Overcoming T790M-driven Acquired Resistance to EGFR-TKIs in NSCLC with Afatinib: A Case Report. Issue 1 (January 2014) - Bordi, Paola; Tiseo, Marcello; Bortesi, Beatrice; Naldi, Nadia; Buti, Sebastiano; Ardizzoni, Andrea
The identification of activating EGFR gene mutations and the availability of effective target therapies such as gefitinib and erlotinib have radically changed the therapeutic approach and prognosis for patients with advanced EGFR-mutated non-small cell lung cancer (NSCLC). However, despite an initial response to EGFR tyrosine kinase inhibitors (TKIs), acquired resistance inevitably develops and the way to overcome it is an open challenge. We report the first case, to our knowledge, of a patient affected by metastatic EGFR-mutated NSCLC with T790M-driven acquired TKI resistance who obtained a significant response to afatinib. Considering the improvement achieved in all disease sites but those in the brain, this case puts a strain on afatinib's activity on brain metastases.